Development of Blended Learning Modules to Improve Critically and Creativity Thinking of Students - Desi Kusumawati; P Purwandari; Titin Kuntum Mandalawati (STAI Hubbulwathan Duri, 2023)
This study aims to develop a blended learning module for health behaviour and ethics courses to improve critical and creative thinking for students of the faculty of health and science. This research refers to the 4-D development model. The research data were obtained from the population of first-semester students of the faculty of health and science who took courses in health behavior and ethics. The samples of this study were students from the health and science faculty of UNIPMA, namely class 1A of the Pharmacy Study Program, which amounted to 18, and class 1A of the Sports Science Study Program, which amounted to 17, bringing the total combined class to 35 students. Data were collected utilizing observation, tests, and questionnaires. Data analysis was carried out using descriptive statistical analysis techniques. The results showed that the Blended Learning Module was developed to improve students' critical and creative thinking skills during the Covid-19 pandemic.